2001
DOI: 10.1097/00000539-200104000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Thoracic Epidural Analgesia with Bupivacaine 0.25% on Ventilatory Mechanics in Patients with Severe Chronic Obstructive Pulmonary Disease

Abstract: Thoracic epidural anesthesia with bupivacaine 0.25% does not impair ventilatory mechanics and inspiratory respiratory muscle strength in severely limited chronic obstructive pulmonary disease patients. Thus, thoracic epidural anesthesia can be used safely in patients with end-stage chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 20 publications
2
27
0
7
Order By: Relevance
“…Pero cuando los estudios son dirigidos a medir el efecto sobre el tono bronquial, se ha visto que el VEF 1 cae (16%) al usar una alta concentración de anestésicos locales (ropivacaina 0,75%) 50 pero que con una concentración menor (ropivacaina 0,25%) se produce incluso disminución de la resistencia de la vía aérea y aumento del flujo inspiratorio 51 . El hecho de que en el sistema respiratorio los receptores beta 1, asociados a las dendritas nerviosas terminales, son mucho menos prevalentes que los beta 2 (1:20), explica porqué el bloqueo simpático regional no provoca aumento del tono bronquial en tér-minos clínicos, lo que podría implicar que la caída del VEF 1 se debe al compromiso muscular causado por el uso de anestésico local más concentrado.…”
Section: Complicaciones Respiratorias Perioperatoriasunclassified
“…Pero cuando los estudios son dirigidos a medir el efecto sobre el tono bronquial, se ha visto que el VEF 1 cae (16%) al usar una alta concentración de anestésicos locales (ropivacaina 0,75%) 50 pero que con una concentración menor (ropivacaina 0,25%) se produce incluso disminución de la resistencia de la vía aérea y aumento del flujo inspiratorio 51 . El hecho de que en el sistema respiratorio los receptores beta 1, asociados a las dendritas nerviosas terminales, son mucho menos prevalentes que los beta 2 (1:20), explica porqué el bloqueo simpático regional no provoca aumento del tono bronquial en tér-minos clínicos, lo que podría implicar que la caída del VEF 1 se debe al compromiso muscular causado por el uso de anestésico local más concentrado.…”
Section: Complicaciones Respiratorias Perioperatoriasunclassified
“…However, it has been demonstrated that epidural analgesia does not impair respiratory muscle strength or airway flow even in patients with end-stage chronic obstructive pulmonary disease, resulting, by contrast, in better ventilatory mechanics and optimal respiratory muscle force generation (Groeben et al, 2002;Gruber et al, 2001;Waurick & Van Aken, 2005).…”
Section: Effect Of Epidural Analgesia On Pulmonary Functionmentioning
confidence: 99%
“…Thoracic epidural anaesthesia appears to have only limited deleterious effects on pulmonary function in patients with severe COPD [73] and has been used as the primary mode of anaesthesia for COPD patients undergoing chest wall surgery [74].…”
Section: Of 222mentioning
confidence: 99%